Optimal germination methods, ornamental plant features, and ex situ conservation of endemic Campanula grandis Fisch & C.A. Mey - Yücel, Gül; Erken, Kamil (Journal of Environmental Engineering and Landscape Management, 2023)
This study aimed to investigate the ornamental utilization, two-year growth performance in natural habitat and cultural conditions, generative production methods, and morphologic and phenologic plant properties of Campanula grandis, which is an endemic species demonstrating ornamental plant potential and needs ex-situ conservation and cultivation. In addition, the germination and growth performance of seeds collected in the new season was compared with seeds that were kept for one year. Seeds stored dry for 3 months at 4 °C and then treated with 200 ppm GA3 exhibited the highest germination percentage (76%). Furthermore, GA3 treated seeds had best germination speed, shortening the germination time. This study also identified the ideal temperature for germination as 20 °C for the best germination rate. It was revealed that the number of flowers on the plant in natural habitat was 48 while in cultural conditions it was found as 165 flowers in biennial plants. The seedlings were planted in an ex-situ collection garden established for placing the Campanula grandis species under conservation. The Campanula grandis species has the potential for use as an ornamental plant for landscaping applications due to its lengthy flowering period, vigorous second-year stem growth, and numerous, enormous, flamboyant, blue-purple, and bell-shaped flowers.